An ethnobotanical survey of traditionally used plants on Suva planina mountain (south-eastern Serbia). (4th December 2015) - Jarić, Snežana; Mačukanović-Jocić, Marina; Djurdjević, Lola; Mitrović, Miroslava; Kostić, Olga; Karadžić, Branko; Pavlović, Pavle
Abstract: Ethnopharmacological relevance: This study documents the ethnobotanical and ethnomedicinal importance of plants in the Suva planina mountain region (south-eastern Serbia). It is reflected in their high diversity and their wide range of uses in the treatment of the local population. The aim of this study was a comparative analysis of data collected in the Suva planina region with relevant data from the Western Balkans, which included identifying the 'most popular' plants, as well as those species which are used specifically for treatment solely in the research area. Materials and methods: Ethnobotanical research was carried out between 2012 and 2014 and data was collected through both open and semi-structured interviews with locals. A total of 66 people were interviewed (37 women and 29 men), aged between 49 and 90 (with a mean age of 71). Results: This study identified 128 plants and 2 fungi which are used in ethnomedicine, 5 plant species used in ethnoveterinary medicine, and 16 plants used for 'other' purposes. Lamiaceae (20), Asteraceae (17), Rosaceae (16), Brassicaceae (5), Alliaceae (4) and Apiaceae (4) have the greatest diversity of species. Results showed that Achillea mellefolium, Allium cepa, Allium sativum, Arctostaphyllos uva-ursi, Gentiana lutea, Hypericum perforatum, Juglans regia, Matricaria chamomilla, Mentha piperita, Plantago lanceolata, Plantago major, Salvia officinalis, Sempervivum tectorum, Tilia cordata and Thymus sepyllum are the 'most popular' medicinal plants (UV=1). Those plants with the most phytotherapeutic uses are Gentiana cruciata (14), H. perforatum (11) and A. sativum (10), while the most common conditions treated with medicinal plants are respiratory (79), urogenital (53), gastrointestinal (51), skin (43) and those relating to the circulatory system (35). A comparative analysis of the data collected in the research area and that from other parts of the Western Balkans showed that there are great similarities within Serbia between Suva planina and the Zlatibor region (37.2%) and Kopaonik Mt. (32.3%), while further afield it is most similar to Bosnia and Herzegovina (40.9%) and Bulgaria (40.6%). Moreover, it was established that 14 plant species and 2 fungi are used only in the Suva planina region, which points to the specificity of the diversity and the sound knowledge of medicinal plants in this region. Conclusions: Our results confirm that medicinal plants are an invaluable resource of the research area and need to be protected as they contribute to an improvement in living standards and the survival of people threatened by unfavourable demographic trends. However, due to over-exploitation, some plants have become exceptionally rare and are under threat, leading to the need for their rational use and protection so as to ensure they are still around for future generations. Graphical abstract: